Advances in human factors, sustainable urban planning and infrastructure : proceedings of the AHFE 2017 International Conference on Human Factors, Sustainable Urban Planning and Infrastructure, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors, Sustainable Urban Planning and Infrastructure, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available